Lonomia obliqua venom action on fibrinolytic system - Fritzen, Márcio (2003)
Accidental skin contact with the Lonomia caterpillar bristles causes a severe hemorrhagic syndrome. While fibrinolytic activation is considered to be the main cause of hemorrhage in Lonomia achelous envenomation, a consumptive coagulopathy was found to be a major component involved in the bleeding complications observed in patients envenomed by contact with Lonomia obliqua. Although we have previously observed that in L. obliqua envenomations, fibrinolysis activation appeared to be secondary to coagulation system activation, there are no reports regarding the ability of L. obliqua venom to activate directly fibrinolytic pathways. We examined the action of L. obliqua crude bristles extract (LOCBE) on several fibrinolytic system components. We demonstrated that LOCBE degraded the A-alpha fibrinogen chain only at high concentrations and after long incubation times. Under these conditions, LOCBE also induced prolongation of the fibrinogen clotting time, but no clot lysis was observed before 24 h. LOCBE did not contain t-PA- or u-PA-like activities. Gel filtration and SDS-PAGE showed that LOCBE did not induce FXIII digestion. In addition, no FXIII activity inhibition was detected by dansylcadaverin method. FXIII levels remained unchanged when FXIII was measured in fibrinogen-depleted LOCBE-treated rat plasma, suggesting that the observed 50% FXIII reduction in rats was related to consumption. In conclusion, our results clearly demonstrated that LOCBE did not display either FXIII inhibition or degradation nor fibrinolytic activity. Furthermore, although proteolytic activity on Aα fibrinogen chain was observed, cross-linked fibrin was not affected by LOCBE. © 2003 Elsevier Ltd. All rights reserved.